2017
DOI: 10.5539/mas.v11n12p84
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Customer Relationship Management on Enhancing the Customers’ Satisfaction in the Banks in Palestine

Abstract: The aim of this paper is to investigate the role of customer relationship management on customers' satisfaction in the banks in Palestine. The primary data was collected from Palestinian Banking Employees. Based on the multiple regression analysis and person correlation tests, this paper finds these results that the regression indicated these two predictors: CRM system integration and Service quality explained 64.2% of the variance (R²= 0.642, F (5,223) =50.222, P< 0.05). The scholars' found that service quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…According to Iriqat and Daqar (2017b) in their study, the impact of CRM has influencing factors, such as service quality, employee's behavior and customer's database on long-term customer loyalty, this study finds a positive relationship between both variables, and a strong impact on employee's behavior and loyalty; which means if employee's deal fair enough with consumers, they will be satisfied. As a result, they will become loyal.…”
Section: Crm Customer Loyalty and Satisfactionmentioning
confidence: 89%
“…According to Iriqat and Daqar (2017b) in their study, the impact of CRM has influencing factors, such as service quality, employee's behavior and customer's database on long-term customer loyalty, this study finds a positive relationship between both variables, and a strong impact on employee's behavior and loyalty; which means if employee's deal fair enough with consumers, they will be satisfied. As a result, they will become loyal.…”
Section: Crm Customer Loyalty and Satisfactionmentioning
confidence: 89%
“…Many prior studies have emphasied on the role and effect of service quality and behavior of employees on the effciency of the firms. Even, many researchers have studied these aspects as factors within the CRM system.Positive word-of-mouth from a satisfied customer can be a zero-investment advertisement agent (Iriqat and Daqar, 2017). However, in today's contactless-yet-connected world, it is necessary to evaluate the role played by these factors(viz.…”
Section: Relevance Of the Studymentioning
confidence: 99%
“…Further, customer satisfaction is a more individualistic phenomenon as the preferences and need of each customer vary from individual to individual (Popovich, 2003). Iriqat and Daqar (2017) have outlined customer satisfaction as a measure to evaluate if the product or service bundle supplied by the organization converges or surpasses the expectations of the customer or not. It acts as a parameter to assess the firm's position in the market and a yardstick for improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Again, Hassani et al [50] collected and analyzed the data sources, research focus, technologies being used, and data analytical tools, giving a better understanding of DM's application in the banking sector. Iriqat and Daqar [51] determined the role of CRM on customer satisfaction in the banking sector of Palestine. The data collected showed that the two predictors-service quality and CRM system integration-explained 64.2%v of the variance showing a positive impact on customer satisfaction.…”
Section: Business-specific Crm Applicationsmentioning
confidence: 99%